ISOLATION AND IDENTIFICATION OF PHYTOSTEROLS FROM BIGNONIA VENUSTA (L.) - Sharma, Manoj (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: To isolate phytosterols from Bignonia venusta (L.) and its antimicrobial activity. Introduction: B. venusta is an important medicinal plant known for its vast potential. It is a valuable plant which is commonly used in traditional system of medicine for relieving pain and inflammation, as well as in a number of metabolic disorders such as diabetes and obesity. Methods: In the present study, phytosterols from B. venusta was identified and quantified in vivo. Phytosterols were identified using chromatographic and spectral studies. Results: Trimethyl (3,3-difluoro-2-propenyl) silane, butanoic acid, 3-methyl-3-nitroso-, methyl ester, peroxide, dibutyl, and 1,2-epoxy-5,5-dimethyl1-phenyl-3-hexyne were identified by infrared and gas chromatography-mass spectroscopy (GC-MS). GC-MS profiling showed various compounds. It is the first report on phytosterols from the experimental plant. Further, we studied antimicrobial potential of isolated compounds against clinically important microbes. Conclusion: B. venusta (L.) is an ideal source of phytosterols and act as antimicrobial agent